Design, Fabrication, and Testing of a Sensor-Driven Table Tennis Trainer with Real-Time Feedback - Stivan Delon Sahertian; Fahriza Fadhila; Johan Kim; Jonathan Bryan; Samuel Theodore Gunawan; Hans Sebastian; Nikolas Krisma Hadi Fernandez; Farid Triawan (JMES: The International Journal of Mechanical Engineering and Sciences, 2026)
This paper presents the design, fabrication, and testing of a sensor-driven training device for table tennis that provides real-time feedback. To identify ball trajectory and validate shots, the device uses infrared and sound sensors in combination with ESP32 microcontrollers in a master-slave arrangement. A goal-like structure attached to the table collects balls, while sensors assess whether a shot is valid, which is defined as a ball that bounces on the table before entering the goal. Visual feedback is provided via LED strips and an LCD display, guaranteeing that players receive immediate and intuitive performance information. Testing was done under three different conditions: infrared sensor only, infrared plus sound sensor in a quiet area, and infrared plus sound sensor in a noisy environment. The results demonstrated that, while a single infrared sensor reliably identified ball entry, it could not distinguishbetween valid and invalid shots. Combining infrared and sound sensors yielded complete accuracy in calm situations but dropped to 40% accuracy in noisy environments due to sound interference. The study addresses the lack of affordable, real-time training feedback systems for table tennis by proposing multi-sensor systems capable of distinguishing valid and invalid shots based on the contact between the ball and the table. This paper reports a validation of the proof-of-concept of a low-cost multi-sensor system, which focuses on the system’s accuracy instead of comparison of human performance.